"Thou shalt not covet ...": Prohibitions, temptation and moral values - Matteo Cervellati; Paolo Vanin (Institute for the Study of Labor (IZA), 2013)
This paper proposes a theory of the relationship between prohibitions and temptation. In presence of self-control problems, moral values may increase individual material welfare (and utility) by serving as a self-commitment device. The model investigates the relationship between morality and temptation, the individual gains from morality, the interaction between external sanctions and moral self-punishment and the spread and strength of individually optimal moral values. The empirical analysis, based on survey data for a large set of countries, documents a hump-shaped pattern of morality in social class, which supports the theoretical predictions of the model.
Keywords: D03; K42; Z13; 330; prohibitions; temptation; self-control; moral values; crime